Prevalence and Factors Related to Nomophobia: Arising Issues among Young Adults - Elissavet Vagka; Charalambos Gnardellis; Areti Lagiou; Venetia Notara (MDPI AG, 2023)
Nomophobia is characterized as apprehension of being apart from smartphone, which causes the user to seek proximity with the device. The purpose of this study was to explore the prevalence and factors associated to nomophobia among young adults in Athens, the capital city of Greece. A cross-sectional study was performed on a sample of 1408 young adults aged 18-25 years. The questionnaire was anonymous, including the socio-demographic characteristics of the participants, the smartphone uses, and the nomophobia questions. Statistical analyses were done by simple univariable techniques or modeling the data through generalized linear models. Almost all participants (99.9%) exhibited any level of nomophobia, with the moderate level prevailing (57.0%). Women and non-working participants were more likely to exhibit severe nomophobia (adj PR = 1.57) and any level of nomophobia was 30% higher among the participants whose father had no academic degree (p = 0.029). In addition, 59% of those with severe nomophobia had very frequent phone checking (p < 0.001) while 45.8% with any level of nomophobia reported a negative influence on their academic performance. Attention should be paid to early prevention through the development of integrated health promotion programs.